Shear connection of prefabricated ultra-lightweight concrete slab systems (PUSSTM). (February 2022) - Ahmed, Inas Mahmood; Tsavdaridis, Konstantinos Daniel
Abstract: This paper reports a detailed computational study of a recently developed novel steel–concrete composite flooring system (PUSS) with two different types of shear connectors: (i) web-welded shear stud connectors (WWSS), and (ii) web-welded shear stud with dowels (WWSS with dowels). In addition, different types of concrete, (normal and lightweight, ) are used. A nonlinear FE model is developed and validated against two sets of full-scale push-out tests of the novel steel–concrete composite flooring system reported in a companion paper. The FE model replicated the experimentally determined failure loads, ultimate slips, and observed failure modes. Parametric studies are conducted to obtain the failure loads and ultimate slips of these PUSS untis with different types of concrete: normal weight concrete, light weight concrete and ultra light weight concrete (NWC, LWC and ULWC), and various diameters and heights of shear connectors (WWSS, WWSS with dowels). The concrete strength varied between 20 N/mm 2 to 35 N/mm 2, the shear connectors' diameter varied between 16 mm, 19 mm, 20 mm and 22 mm, and the height of the shear studs between 75 mm and 100 mm. In conclusion, load-slip curves obtained from the FE parametric studies demonstrated that FE models with same diameter of shear connectors can result to different slip stiffnesses, while the failure loads and slips varied with the concrete strengths. The slip results were also compared with different shear connection systems' dimensions at concrete strengths of 20, 30 and 35 N/mm 2 .